Pexidartinib synergize PD-1 antibody through inhibiting treg infiltration by reducing TAM-derived CCL22 in lung adenocarcinoma - Zhang, Wei; Jiang, Xi; Zou, Youcheng; Yuan, Lihua; Wang, Xiaobo (Frontiers in Pharmacology, 2023)
There is a crosstalk between Tumor-associated macrophages (TAM) and tumor-infiltrating T cells in tumor environment. TAM could inhibit the activity of cytotoxic T cells; TAM could also regulate the composition of T cells in tumor immune environment. The combination therapy for TAM and tumor infiltrated T cells has been widely noticed, but the crosstalk between TAM and tumor infiltrated T cells remains unclear in the process of combination therapy. We treated lung adenocarcinoma tumor models with pexidartinib, which targets macrophage colony stimulating factor receptor (M-CSFR) and c-kit tyrosine kinase, to inhibited TAM. Pexidartinib inhibited the ratio of macrophages in the tumor and also altered macrophage polarization. In addition to reprogram TAM, pexidartinib also changed the composition of tumor-invasive T cells. After pexidartinib treatment, the total number of T cells, CD8+ T cells and Treg cells were all decreased, the ratio of CD8+T / Treg increased significantly. According to the analysis of cytokines and chemokines during the treatment of pexidartinib, CCL22, as a chemokine for Treg recruitment, significantly decreased after the treatment of pexidartinib. Base on the above observation, the combination of pexidartinib and PD-1 antibody were used in the treatment of lung adenocarcinoma subcutaneous tumor model, the combination therapy has significantly improved the efficacy of tumor treatment compared with the monotherapy. Meanwhile, compared with pexidartinib monotherapy, the combination treatment further switches the polarization status of tumor-associated macrophages. In summary, our results showed that the combination of pexidartinib and PD-1 antibody showed a synergy and significantly improved the anti-tumor efficacy, through pexidartinib increasing CD8T/Treg ratio by reducing TAM-derived CCL22.